Tragedy of Errors- An Analysis of Human Factor in Medical Errors - Manika Agarwal; Sharat Agarwal (Journal of Clinical and Diagnostic Research, 2020)
William Shakespeare wrote a play “Comedy of error”, but this is about medical error which may often result in tragic outcome. We often read about medical errors and sometimes realise in our clinical practice that an error has been committed by us or our team leading to an adverse event. Sometimes, these errors are due to lack of knowledge and sometimes due to improper communication and misinterpretations. The aim of this manuscript is to analyse the causes of medical errors, which may vary from irrational prescription, attitudes of arrogance in seniors and juniors leading to communication gaps, bad hand writings or wrong patient selection for surgical intervention for economic benefits. Use of Artificial intelligence, Data mining and Medical informatics can rectify errors of improper assessment and irrational prescription. Self-introspection and spirituality can prevent errors arising from attitudes of arrogance, fear, greed and pride in medical professional.